A snapshot on molecular technologies for diagnosing FAdV infections - Kardoudi, Amina; Siham, Fellahi; Abdelmounaaim, Allaoui; Faouzi, Kichou; Ikram, Ouchhour; Thomas, Jackson; Abdelouaheb, Benani (Frontiers in Veterinary Science, 2025)
Fowl adenoviruses (FAdV) are prevalent in chickens worldwide, responsible for several poultry diseases, including inclusion body hepatitis (IBH), hepatitis-hydropericardium syndrome (HHS), and gizzard erosion (GE), which result in significant economic losses in the poultry industry. Consequently, detection and efficient identification of FAdV serotypes are becoming extremely urgent to monitor outbreaks and develop vaccination strategies. Conventional PCR (cPCR) tests, combined with Restriction Fragment Length Polymorphism (RFLP) or sequencing, were developed for FAdV diagnosis. Although these molecular tests have considerably improved the accuracy of FAdV diagnosis compared with conventional methods, certain drawbacks remain unresolved, including lack of sensitivity and post-PCR analysis. Subsequently, advanced molecular technologies such as real-time PCR (qPCR), Loop Isothermal Amplification (LAMP), Cross-Priming Amplification (CPA), Recombinase Polymerase Amplification (RPA), Digital Droplet Polymerase Chain Reaction (ddPCR), Dot Blot Assay Combined with cPCR, Nanoparticle-Assisted PCR (nano-PCR), PCR-Refractory Quantitative Amplification (ARMS-qPCR), CRISPR/Cas13a Technology, and High-Resolution Melting Curve (HRM), have been developed to improve FAdV diagnosis.